Effect of the particle size and the debinding process on the density of alumina ceramics fabricated by 3D printing based on stereolithography - Wu, Haidong; Cheng, Yanling; Liu, Wei; He, Rongxuan; Zhou, Maopeng; Wu, Shanghua; Song, Xuan; Chen, Yong (Ceramics international, 2016)
In this study, Al2O3 ceramics were printed by stereolithography from particles with different particle size distributions, which are the micro-sized Al2O3, nano-sized Al2O3, and a mixture of both. The influence of the particle size and the debinding method on the density and morphology of the sintered bodies were investigated. The density of the samples containing both micro-sized and nano-sized alumina particles is highest among the three samples. Furthermore, the samples subjected to the vacuum debinding showed a higher density compared with the samples subjected to the traditional thermal debinding. The results suggest that the combination of a powder with a bimodal particle size distribution and the vacuum debinding process offers an effective way to print 3D ceramics with a good performance through stereolithography.